A.ÁBDIEVTÍŃ «IYT HÁM ADAM YAMASA AShLÍQ SÍNAǴÍ» POVESTINDE INSAN TÁǴDIRI - Ktaybekova, Zulfiya Kengesbaevna (SCIENCE and SOCIETY, 2026)
The ideological and thematic directions, plot-compositional features, and poetics of A. Abdiev's story "The Dog and the Man, or the Trial of Hunger" are analyzed. In the story, the writer reveals the tragic life of a single person. The work also analyzes the relationship between man and animal, nature and man through examples.